PROTEIN SEPARATION BY ISOELECTRIC PRECIPITATION USING HIGH PRESSURIZED CO2 IN THE FRAMEWORK OF MICROALGAE BIOREFINERY - Viendra Permana, Ellsie
Microalga nowadays are one of the most potential renewable sources of biomass to fulfill the world’s needs of fuels due that it does not compete with agricultural commodities due its high growing rate, and it is able to utilize waste CO2 streams. In spite of the microalga potential as a renewable resource, production capacity of microalgae is limited by the production and maintenance cost compared to land- based crops. In addition, the capital investment and operational costs make not possible so far the industrialization of microalgae for massive biofuel production. Therefore, alternative by-products from microalgae are compulsory. Among all the cell constituents, proteins amount up 20-40% of the total microalgae biomass, which is interesting as a product due to the high concentration in the cell and its attractive commercial value. Microalgae protein can be saw as amino acid source for animal feeding, food enrichment, or could be the source of more specialized compounds (i.e. food specialties and pharmaceutical products). Thus, this thesis explores the potential use of carbon dioxide as a precipitant agent for bulk protein microalgae recovery. Desmodesmus sp. was used as model algae for protein isoelectric precipitation and the work is focus on the effect of the protein extraction environment on the further CO2 precipitation stage. At 40 bars, 18 0C, and 60 minutes up to 29wt% of first extraction protein and 45wt% of second extraction protein could be precipitated by CO2. It was found that the environment for the protein extraction has an enormous effect on the protein precipitation yield. Indeed, the use of protein extraction additives such as surfactant (Tween-80), buffer solution (phosphate buffer), and sodium chloride, although increase the extraction of protein out of the cell debris after milling, they hinder the CO2 precipitation leaving to low precipitation yield (11.6 – 19.8 wt%). In this protein precipitation by using pressurized CO2, protein structure was successfully recovered 54-76wt% of PP after precipitation, where RuBisCO was the main product present into the final solution. This work discusses the results